Dermoid cyst, unusual location of the pterion: About a case and review of literature - Salma Abbas, MD; Thameen Jaradat, MD; Mahjouba Boutarbouch, MD, PhD; Nadia Cherradi, MD, PhD; Abdessamad El Ouahabi, MD, PhD (Radiology Case Reports, 2024)
Intracranial dermoid cysts are benign tumors of congenital origin. The intradiploic forms are rare, exceptional at the pterional level. We report the case of a 10-year-old girl who presented with a cutaneous fistula in the left frontotemporal region. The blind end of the fistula was an intradiploic dermoid cyst in the rare location of the pterion confirmed by imaging and histopathology. Once this lesion is suspected, it is important to identify its location and morphology using imaging techniques and to complete excision of the cyst to avoid complications associated with infection and to mitigate the risk of subtotal resection.